Hubungan Antara Self-Monitoring dengan Prokrastinasi Akademik pada Siswa SMA Muhammadiyah 2 Sidoarjo - Putra, Dhimas Jayadiningrat Haji; Affandi, Ghozali Rusyid (ResearchJet Journal of Analysis and Inventions, 2024)
This research is motivated by the phenomenon of academic procrastination experienced by students of SMA Muhammadiyah 2 Sidoarjo. This study aims to determine the relationship between self-monitoring and academic procrastination in students of SMA Muhammadiyah 2 Sidoarjo. This research belongs to the type of quantitative research with a correlational approach. The population in this study amounted to 1257 students, so from the calculation using the krejcie Morgan formula the sample used was 297 students who were taken using stratified random sampling technique. Data collection in this study used two psychological scales, namely the self-monitoring scale from the self-monitoring aspect and the academic procrastination scale from the academic procrastination aspect. Data analysis in this study used Spearman's Correlations and the analysis process used the help of the JASP program version 0.13.1.0 for windows. The results showed that the value of r = -0.163 and the value of p = 0.005 where 0.005 <0.05, which means that there is a negative relationship between self-monitoring variables and academic procrastination in students of SMA Muhammadiyah 2 Sidoarjo.